Digital Political Communication Strategy of MULIA on Instagram: A Political Branding Perspective in the Makassar Mayoral Election - Rahmawati Haruna; Sitti Rabiatul Wahdaniyah Herman; Agung Nugraha (State Islamic Institute of Bone, Indonesia, 2025)
The rapid development of digital media has transformed polit ical communication, particularly in local elections where social media function not only as channels of information but also as spaces for constructing political narratives and voter engagement. This study analyzes the digital political communication strategy of the MULIA candidate pair Munafri Arifuddin and Aliyah Mustika Ilham through Instagram during the Makassar mayoral election. Using a qualitative approach, this research applies critical discourse analysis developed by Norman Fairclough combined with agenda-setting theory from Maxwell McCombs and Donald Shaw. Data were collected through digital observation, documentation of campaign materials, and interviews with the campaign media team. A total of 419 Instagram posts published during the campaign period were analyzed to identify patterns of issue framing, political image construction, and digital campaign strategies. The findings show that the campaign implemented structured communication strategies including strategic issue selection, agenda setting, political marketing stages (awareness, likeability, and electability), and emotional branding through Hero and Caregiver archetypes. Instagram functioned not merely as a dissemination tool but as a discursive arena where political identity, legitimacy, and emotional connections with voters were constructed. The study highlights the growing importance of digital political communication in shaping public perception and influencing electoral participation in local democratic contests.